CROSSWORD PUZZLE THERAPY AS A COGNITIVE ENCHANCEMENT INTERVENTIONFOR THE ELDERLY - Dwinita Aprilia Safitri; Rachmawaty M. Neor; Cut Putro Azzahara Cut; Yulianti Wulandari (Poltekkes Kemenkes Banten, 2026)
The aging process experienced by the elderly causes problems in their physical, mental, and behavioral development. The physical ability of the elderly decreases with age, which causes problems with decreased cognitive function in the elderly. One of the interventions that can be done in the elderly to stop the decline in cognitive function is Crossword Puzzle Therapy (CPT) which can improve cognitive ability, improve memory, and improve comprehension. To determine the effect of Crossword Puzzle Therapy (CPT) on the cognitive function of the elderly in the Working Area of the Tanjung Unggat Health Center, Tanjungpinang City. The research method used quasy experimental design with the One Groups PretestPosttest Design approach. The sample in the study was 33 elderly people who were treated at the Tanjung Unggat Health Center in Tanjungpinang City and the sampling technique was a purposive sampling technique. This study uses a normality test with a sig. > 0.005 and continued with a non- parametric test, namely the Wilcoxon test. The results of the study are known to have a P value which shows a number of 0.000 which means that the significant value is < 0.05 value so that Crossword Puzzle Therapy (CPT) on cognitive function has a significant influence, namely H0 is rejected and Ha is accepted. There is an effect of Crossword Puzzle Therapy (CPT) on cognitive function in the working area of the Tanjungunggat Health Center in Tanjungpinang City with a P value of 0.000. it is hoped that the health center can apply Crossword Puzzle Therapy (CPT) in improving the quality of health of the elderly, especially in handling the cognitive function of the elderly.